ASSISTED REPRODUCTIVE TECHNOLOGY BETWEEN MEDICINE, RELIGION AND LAW - Dan LUPAȘCU; Ioana PĂDURARIU (Challenges of the Knowledge Society)
The new, the engine that allows us to evolve. That is what we do by nature: we figure out how things work and we make new steps, over and over. We created vaccines to help prevent diseases and, in the future, maybe we are about to create a human being outside the womb. It is a sin, it is a legal thing, it is moral? Are we guilty of considering ourselves gods? Medically assisted human reproduction is a piece of a puzzle, of an engine that can separate us or bring us together, that can raise or erase family boundaries, give us rights or put us on the wall of morality. Assisted reproductive technologies are medical procedures and their role is, first of all, to help people who experience some difficulties or who suffer an inability to have biological children of their own. But the access to the experience of pregnancy is expanded by the big new development to the potential of those reproductive technologies. And, as always, there is a price for that, for everything that we create or update, and those challenges go far beyond medicine, science or pure technique and we are forced to wonder about moral, religious or legal limitations.